Inhibition of FAK Signaling Elicits Lamin A/C-Associated Nuclear Deformity and Cellular Senescence - Chuang, Hsiang-Hao; Wang, Pei-Hui; Niu, Sheng-Wen; Zhen, Yen-Yi; Huang, Ming-Shyan; Hsiao, Michael; Yang, Chih-Jen (Frontiers in Oncology, 2019)
Focal adhesion kinase (FAK) is a nonreceptor kinase that facilitates tumor aggressiveness. The effects of FAK inhibition include arresting proliferation, limiting metastasis, and inhibiting angiogenesis. PF-573228 is an ATP-competitive inhibitor of FAK. Treating lung cancer cells with PF-573228 resulted in FAK inactivation and changes in the expressions of lamin A/C and nuclear deformity. Since lamin A/C downregulation or deficiency was associated with cellular senescence, the senescence-associated β-galactosidase (SA-β-gal) assay was used to investigate whether PF-573228 treatment drove cellular senescence, which showed more SA-β-gal-positive cells in culture. p53 is known to play a pivotal role in mediating the progression of cellular senescence, and the PF-573228-treated lung cancer cells resulted in a higher p53 expression level. Subsequently, the FAK depletion in lung cancer cells was employed to confirm the role of FAK inhibition on cellular senescence. FAK depletion and pharmacological inhibition of lung cancer cells elicited similar patterns of cellular senescence, lamin A/C downregulation and p53 upregulation, implying that FAK signaling is associated with the expression of p53 and the maintenance of lamin A/C levels to shape regular nuclear morphology and manage anti-senescence. Conversely, FAK inactivation led to p53 upregulation, disorganization of the nuclear matrix, and consequently cellular senescence. Our data suggest a new FAK signaling pathway, in that abolishing FAK signaling can activate the senescence program in cells. Triggering cellular senescence could be a new therapeutic approach to limit tumor growth.